(untitled) (Journal of Naval Architecture and Marine Engineering, 2018)
The aim of present study is to analyze the non- Darcian effects on unsteady non-linear MHD flow of an incompressible, electrically conducting and viscous fluid over a stretching sheet embedded in a porous medium with heat source, viscous dissipation and thermal stratification. The dimensionless governing equation solved numerically by using 4th order Runge - Kutta method. The effects of pertinent parameters on velocity and temperature depicted graphically.